MENINGKATKAN KEMAMPUAN SKILL LAB SYRINGE PUMP MELALUI VIDEO TUTORIAL: Improving The Skill Lab of Syringe Pump Through Video Tutorials - Rachmat Chusnul Choeron; Wahyu Dini Metrikayanto (LPPM STIKES Pemkab Jombang, 2022)
Introduction. The syringe pump lab skill is one of the nurse's professional student competencies. However, many students have difficulty mastering these competencies, especially during the COVID-19 pandemic which makes it impossible to meet directly between students and lecturers. The purpose of this study was to prove the effect of online video tutorials on the ability of nursing profession students' lab skills. Methods. This study uses a one group pre-post test design. The population in this study were students of Nursing Professional Education, Faculty of Health Sciences, Tribhuwana Tunggadewi University. A sample of 53 respondents was taken randomly. The independent variable in this study was an online video tutorial, while the dependent variable was the ability of the syringe pump lab skill. The research instrument used an observation sheet. Data were analyzed using paired t test with =0.05. Results. The results of this study found that the average value of the syringe pump lab skills of professional students before being given an online video tutorial was 68.82 (SD = 8.93), the average value of the syringe pump lab skill of professional students after being given an online video tutorial was 78.55 (SD=4.58) and there was a significant effect of online tutorial videos on the ability of the syringe pump lab skills (p=0.000; = -9.73; SD=6.60; r=0.699). Discussions. Online video tutorials can be an effective option in teaching various lab skills to nursing professional students.